Reacciones adversas a medicamentos, reportadas en pacientes hospitalizados en el Hospital Víctor Lazarte Echegaray-EsSalud, Trujillo, año 2016 - Muñoz Quispe, Nancy Karolina (2018)
In the present report of pre-professional practices, the identification and determination of Adverse Reactions to drugs reported in hospitalized patients in the Víctor Lazarte Echegaray Hospital - EsSalud, Trujillo, from February to December 2016, is presented, for which the method was used. of spontaneous notification of RAMs, compiling the suspected RAMs of the hospitalization services reported by the Pharmacy Interns in the Hospitalization Hospital. This research is a descriptive, cross-sectional and retrospective study, in which a total of 32 formats of RAMs reports were evaluated, taking into account the age, sex and service of the hospitalized patients, as well as the month of occurrence of each reaction, using, also, the first level of ATC classification, WHO-RAM method for affected organs and systems, the Rawlins and Thompson Classification, severity and finally evolution of the reported adverse reactions. Of the 32 formats of RAMs reported, the greatest number of ADRs occurred in the age group of people over 60 years old, with 46.9% and 63% were female and 38% male. the source of the reports was mainly from the Internal Medicine Service with 66%, the maximum value of notifications was reached in the month of October with 47% of reports of ADR, the Anti-infective in general for systemic use were those that caused the greater number of RAMs, with 44%; where antituberculous drugs and Ciprofloxacin were the most frequent with 21% respectively, according to the WHO-RAM method by affected organs and systems, the most frequent ADRs corresponded to skin disorders and appendices with 24%, pruritus being the Most frequent (28%), according to the Rawlins and Thompson classification, type A ADRs presented a greater frequency with 84%, followed by type B AD with 16%, depending on the severity, mild adverse reactions represented 41% , the moderate ones by 34% and the serious ones by 25% and finally according to the evolution, the majority of the ADRs of the patients hospitalized in the HVLE, had a favorable evolution, they recovered, 63%, and 25% prolonged their hospitalization and still does not recover